PENGARUH MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 1 MALANG - Nuzulul Madalia; Ika Ratih Sulistiani; Dian Mohammad Hakim (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This study aims to (1) determine the learning outcomes of Islamic religious education subjects at SMA Negeri 1 Malang, and (2) determine the effect of learning media on learning outcomes of Islamic religious education subjects at SMA Negeri 1 Malang. The method used in this research is quantitative research with experimental research type. The design of this research is Posttest Control Group Design which consists of 20 students from X Mipa 2 as the control class and 20 students from X Mipa 4 as the experimental class. Data collection techniques used are test and documentation techniques. Testing the normality and homogeneity of the data is a basic requirement before testing the hypothesis. The results of hypothesis testing using the t-test Paired T-test showed that sig. (2-tailed) 0.000 < 0.05, namely Ho is rejected and Ha is accepted. From the results of the t-test, it can be concluded that the learning media has a significant effect on the learning outcomes of Islamic religious education subjects at SMA Negeri 1 Malang.